Kinematics and Transmission Performance Analyses of a 2T2R Type 4-DOF Spatial Parallel Manipulator - Haiyan An; Bin Li; Shoujun Wang; Weimin Ge (Journal of Robotics)
A 2-RPU&2-SPS spatial parallel mechanism (SPM) is researched. Firstly, the number and property of degrees of freedom (DOF) of the SPM are analyzed by screw theory. There are two rotational and two translational movements (2R2T) of the mechanism that can be achieved. Secondly, the position analyses are researched. For the inverse position analysis, the explicit expression can be obtained from the independent motion parameters of the given mechanism, and the forward position problem is solved by calculating a set of nonlinear equation systems. Then we obtained the workspace of the mechanism based on the analytic formulae of the inverse displacement. Finally, by establishing the Jacobian matrix of the mechanism, the singularity of the mechanism is obtained, and the kinematics transmission performance of the mechanism is studied by using the index of the output efficiency of the limb output of the mechanism. This work will provide the theoretical basis for prototype development and application of the mechanism.